Choosing a Life Partner through Social Media: An Analysis from the Perspective of Islamic Law - Bairi Bairi; Dzulfikar Rodafi; Siti Masruchah (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to examine the phenomenon of partner selection through social media in Lerpak Village, Geger District, Bangkalan, by highlighting its positive and negative impacts and examining the practice from an Islamic legal perspective. This study uses a descriptive type with a qualitative approach. Data were collected through library research and field research. Data collection techniques include interviews, observation, and documentation. Data analysis techniques use data collection, data reduction, data presentation, and drawing conclusions. The results of the study are as follows: (1) Searching for a partner through social media in Lerpak Village is starting to become popular and many people are doing it. The media used are Facebook and WhatsApp. From these media they conduct explorations. From these explorations, some have reached marriage and engagement. And some have not continued. (2) The positive impact of searching for a partner on social media in Lerpak Village is getting a partner quickly, more self-confidence, many choices, minimal conflict and no need for intermediaries. While the negative impacts are: identity falsification, misjudgment, and lack of control. (3) Searching for a partner through social media is permissible, because social media is a medium (wasāil) for marriage that can be developed.. So it does not deviate from the concept of maslahah because it does not deviate from the five maqāṣid al-sharī’ah, namely: preserving religion, soul, mind, descendants and property.